TRPC absence induces pro-inflammatory macrophages and gut microbe disorder, sensitizing mice to colitis - Lin, Yanting; Cui, Xinmeng; Cao, Qiuhua; Bi, Ran; Liu, Yiming; Jing, Dongquan; Yue, Chongxiu; Zhao, Qixiang; Wang, Yue; Liu, Siliang; Su, Yali; Formoso, Karina; et al. (International immunopharmacology, 2023)
•Lacking all seven TRPC proteins promoted the development of dextran sulfate sodium (DSS)-induced colitis.•Lacking all seven TRPC proteins recruit macrophages and induce M1 polarization of macrophages.•Mice absence of TRPCs causes bacterial flora disorders, which are pivotal to the detrimental action of TRPC absence to colitis.•Our findings add a better understanding of the role of TRPC channels in colitis, and also hints a possibility for gastrointestinal adverse reactions of drugs that inhibit TRPC channels. The transient receptor potential canonical (TRPC) channels, encoded in seven non-allelic genes, are important contributors to calcium fluxes, are strongly associated with various diseases. Here we explored the consequences of ablating all seven TRPCs in mice focusing on colitis. We discovered that absence of all seven TRPC proteins in mice (TRPC HeptaKO mice) promotes the development of dextran sulfate sodium (DSS)-induced colitis. RNA-sequence analysis highlighted an extremely pro-inflammatory profile in colons of DSS-treated TRPC HeptaKO mice, with an amount of increased pro-inflammatory cytokines and chemokines. Flow cytometry analysis showed that the infiltration of Ly6Chi monocytes and neutrophils in colonic lamina propria was significantly increased in DSS-treated TRPC HeptaKO mice. Results also revealed that macrophages from TRPC HeptaKO mice exhibited M1 polarization and enhanced secretion of pro-inflammatory factors. In addition, the composition of gut microbiota was markedly disturbed in DSS-treated TRPC HeptaKO mice. However, upon antibiotic cocktail (Abx)-treatment, TRPC HeptaKO mice showed no significant differences with WT mice in disease severity. Collectively, these data suggest that ablation of all TRPCs promotes the development of DSS-induced colitis by inducing pro-inflammatory macrophages and gut microbiota disorder.